Dynamic modelling of long-term care decisions - Michelle Sovinsky; Steven Stern (University of Zurich, Department of Economics, 2013)
This paper describes and analyzes research on the dynamics of long-term care and suggests directions for the literature to make progress. We discuss sources and causes of dynamics including inertia/state dependence (confounded by unobserved heterogeneity); match-specific effects; and costs of changing caregivers. We comment on causes of dynamics including learning/human capital accumulation; burnout; and game-playing. We suggest how to deal with endogenous geography; dynamics in discrete and continuous choices; and equilibrium issues (multiple equilibria, dynamic equilibria). Next, we evaluate the advantages of different potential data sources (NLTCS, PSID, AHEAD/HRS, SHARE, ELSA) and identify first order data problems including noisy measures of wealth and family structure. We suggest some methods to handle econometric problems such as endogeneity (work, geography) and measurement error. Finally, we discuss potential policy implications of dynamics including the effect of dynamics on parameter estimates and direct policy implications of inertia (implications for family welfare, parent welfare, child welfare, and cost of government programs).
Keywords: 330; Langzeitpflege; Privater Haushalt; Familie-Beruf; Wohlfahrtsanalyse; Datenqualität; Modellierung